Reflections on Action Research: Uncovering My Assumptions - Monica McGlynn-Stewart (Networks: An Online Journal for Teacher Research, 2003)
I have engaged in action research for several years in different settings and for different purposes. At the elementary level I have used action research to try to understand my students' view of the culture of our classroom, (presentation, OERC, 1996) and to make a geometry unit come alive (International Reading Association, 1996). At the secondary level, I used Action Research to develop a leadership program (Teachers College Press, 2001) and to help my fellow DICEP members and me understand the functioning of our own research group (Orbit, 1998).